Improved cycling performance of prussian blue cathode for sodium ion batteries by controlling operation voltage range. (20th January 2017) - Yan, Xiaomin; Yang, Yang; Liu, Ershuai; Sun, Liqi; Wang, Hong; Liao, Xiao-Zhen; He, Yushi; Ma, Zi-Feng
Abstract: Prussian blue and its analogues have been intensively studied as potential electrode materials for sodium ion batteries. In this work, a prussian blue sample was prepared by a simple precipitation method and the electrochemical performance of the prussian blue (PB) cathode was investigated at various temperatures and in different voltage ranges. When cycled in the voltage range of 2.0 − 4.0 V vs. Na/Na +, the PB cathode exhibited initial discharge capacities of 135.4 mAh g −1 (55 °C), 128.5 mAh g −1 (25 °C) and 99.2 mAh g −1 (-10 °C) at 10 mA g −1 . The PB cathode showed good cycling stability at low temperature, however the cycling capacity degraded remarkably at elevated temperature. CV test indicated that the capacity fade was mainly due to the side reactions on the electrode-electrolyte interface at near 4.0 V vs. Na/Na + . XPS and FTIR analyses revealed several types of compounds formed on the cathode surface which indicated the complexity of the side reactions. Controlling the high cut-off voltage at 3.8 V vs. Na/Na + significantly improved the cycling stability of the PB electrode. The PB cathode delivered 1C rate reversible capacity of 100.0 mAh g −1 in 2.0 − 3.8 V vs. Na/Na + with outstanding capacity retention of 98.2% after 300 cycles.